(untitled) (South East Asia Journal of Public Health, 2013)
Antenatal care (ANC) includes care during pregnancy, should begin from the early stages of pregnancy. ANC al-lows management of pregnancy, detection and treatment of complications, and promotion of better maternal and child health. This study assessed the factors relating to maternal healthcare practices in rural Bangladesh and exam-ined the association between use of antenatal care services and socio-demographic variables of rural women. A community based cross-sectional study was conducted in Madhupur upazila of Tangail district. Postnatal mothers who visited the Expanded Programme on Immunization (EPI) centers constituted as sampling frame and selected. The sample size was determined based available information on the Bangladesh Demographic and Health Survey (BDHS) 2007. In total 360 randomly selected postnatal mothers were interviewed using structured questionnaire for collecting information on demographic characteristics, knowledge on ANC and practices. The mean (±SD) age of the respondents was 24(±4.4) years. Most (95.6%) of them were housewives. Twenty-two percent of the respon-dents were from the poorest socioeconomic class. Mothers who had one living child had the highest percentage of adequate ANC use compared to those who had two or more living children. Access to mass media (newspapers and TV) had a positive significant (p<0.001) effect on the use of ANC services. The results of logistic regression analy-sis showed that, after adjusting other factors, respondents who had secondary-level education were 4.5 times more likely to use ANC adequately compared to those who had no education. The findings suggested that education of the mothers is an important determinant of ANC visits during pregnancy. Therefore, information, education and communication on ANC must be intensified in order to reach the rural mothers. DOI: http://dx.doi.org/10.3329/seajph.v2i2.15956 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 61-66